(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article researches the aphoristic case which is represented by Lina Kostenko’s literary works. The aphorism as universal way of making language picture of the world and filling in it with deep philosophic meaning is examined. The article approves that aphoristic statements are value translators of author’s world outlook, his socialization. At the same time they are guidelines, which can influence on individual consciousness, correct his behavior and activities, help to realize the human essence, moral improvement, spiritual enrichment, personality development. The national picture of the world is represented by actualization of concepts within the bounds of aphoristic statements that show the priorities of Ukrainian national interests.